O efeito da configuração da estrutura de propriedade nas decisões sobre estrutura de capital: uma análise da empresa brasileira - Pinheiro, Bruno Goes (2025)
In the corporate finance literature, the decision on capital structure is considered one of the most relevant issues, because if an adequate capital structure is applied, the company will maximize its value. In this context, conflicts of interest between shareholders and managers, as well as those between majority and minority shareholders, can affect the way the company is financed for different reasons. These reasons include the use of debt as a mechanism to discipline the company's management and the fear of large shareholders of issuing shares due to the possible loss of control. In this context, this thesis aims to analyze the effect of ownership structure on the capital structure of Brazilian companies. The research used an unbalanced panel of data, made up of 2,643 annual observations from 262 companies listed on the Brazilian stock exchange (Brasil, Bolsa e Balcão - B3), from 2010 to 2022. The data collection used the reference form of the Brazilian Securities and Exchange Commission (CVM) and the Economática® system. Models were estimated using the multiple linear regression method of generalized least squares and logistic regression. The research results corroborate the thesis that the choice of capital structure of Brazilian companies is influenced by the configuration of the ownership structure. Therefore, as hypothesized, the configuration of the ownership structure is a relevant determinant for the capital structure of the Brazilian corporate sector in general. The results show that the concentration of ownership, the different types of shareholder control (dominant, shared and dispersed) and the identity of the main shareholder (non-financial company, family, government and institutional investor) are relevant elements for the agency conflicts of the Brazilian company and have an influence on decisions about corporate financing policy, through debt, debt maturity and the issue of shares. Finally, the thesis contributes to the debate on capital structure decisions by providing additional vidence in a country that is an important emerging market, where companies are characterized by being dependent on bank credit for investments, having high shareholder concentration and a maturing capital market.